Ранньосередньовічні пам’ятки Розточчя в світлі краєзнавчих та археологічних досліджень (ХІХ – 30-ті роки ХХ ст.) - Ляска, В. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
The article deals with history of research of medieval monuments in the territory of Roztochchya from the beginning of ХІХ century – 30-th of XX century. Two successive phases in process of studying of region are distinguished: local history and archaeological. In this context special attention is focused on the characteristics of local history descriptions of the 19-th century – on discussion of the issue of localization of annalistic cities, on the characteristics of the first archaeological excavations in this area. Importance of scientific activities of B. Janush, M. Drevko, J. Pasternak etc. is emphasized.